2014
DOI: 10.1186/1752-1947-8-96
|View full text |Cite
|
Sign up to set email alerts
|

Complementary role of magnetic resonance imaging after ultrasound examination in assessing fetal renal agenesis: a case report

Abstract: IntroductionUltrasonography is used routinely during pregnancy to screen and detect fetal abnormalities. However, there are some conditions like anhydramnios (a prevalent state in renal agenesis) or maternal obesity that may limit the diagnostic accuracy of ultrasonography. Magnetic resonance imaging has proven to be useful when ultrasound alone is insufficient to make a correct diagnosis.Case presentationWe present the case of a 22-year-old Caucasian woman who was admitted to our unit at the 26th week of gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However this only amounted to 54 studies in total as some artices described different tests from the same study. Of the 134 indirect evidence papers or abstracts, 133 were synthesised41–174 as well as a single trial record 175. None of the seven included trials identified from trial registries reported interim or final results and only four remain active 176–179.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However this only amounted to 54 studies in total as some artices described different tests from the same study. Of the 134 indirect evidence papers or abstracts, 133 were synthesised41–174 as well as a single trial record 175. None of the seven included trials identified from trial registries reported interim or final results and only four remain active 176–179.…”
Section: Resultsmentioning
confidence: 99%
“…For both risk of bias and applicability to the review question, the majority (n=129) had some concerns,41 42 44–67 69–87 89–149 151–170 172–174 and five had a high level of concern43 68 88 150 171 (figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second-trimester scan, between 18 and 22 weeks, remains the standard for fetal anatomical assessment worldwide. However, significant improvement in detecting fetal abnormalities in the first trimester of pregnancy is also recognized [4].…”
Section: Introductionmentioning
confidence: 99%